Jogo para capacitação de leigo em parada cardiorrespiratória extra-hospitalar: prototipagem e validação de conteúdo - Bossle, Marivoni Teixeira (Universidade do Vale do Rio dos Sinos, 2021)
Cardiopulmonary arrest (CPA) is a pathology of great proportions in morbimortality. It is estimated that approximately 50% of CPAs occur in an extra-hospital environment and, for most of them, are witnessed by lay people, so it is important that they know how to perform cardiopulmonary resuscitation (CPR) maneuvers. This maneuver is a simple and potentially life-saving method that can be performed by individuals in the community, without the need for equipment or the requirement of being a health professional. To this end, the need for CPR training aimed at the general population is highlighted. Educational technologies (TE) are strategies for building knowledge about Cardiopulmonary Arrest and acquisition of competences to perform CPR by the lay public. Aim: to develop a game, in virtual reality, for the training of lay people in extra-hospital cardiopulmonary arrest. Method: This is a methodological research of technological production, where a EdTech was developed, through serious games, aimed at training lay people in CPR. The study was developed in five stages: stage I consisted of an integrative review (IR) of the literature on the use of serious games in virtual reality for training lay people in CPA outside healthcare facilities. Stage II contemplated a situational diagnosis aiming to know the initiatives of lay people regarding CPA, through a questionnaire made available on social networks. In stage III, following Novak's recommendations, EdTech was developed through the construction of the game entitled “Help: Cardiac Arrest!”, in partnership with experimental studio Atomic Rocket Entertainment of the Technological Bachelor in Digital Games Development at Unisinos. Stage IV consisted in the validation of the EdTech, by expert judges in the health field, with experience in urgency and emergency. Results: the literature review occurred in online databases, published from 2015 to 2020, which resulted in the selection of 6 articles, according to the inclusion criteria. Virtual reality was identified as a promising EdTech for training lay people in CPR. The situational diagnosis showed that 74,9% (n = 281) of the lay people interviewed would not know how to recognize a victim in CPA; 67,5% (n = 253) would not feel able to rescue friends or relatives, and 84,6%; (n = 317) would not perform any type of intervention on a stranger. In the TE validation process, the judges evaluated seventeen items in the three domains (objectives, structure/presentation, and relevance), where there was a level of confidence agreement = 99%, adequacy index of each item = 95%, and proportional difference = 10%, as for the internal consistency analysis of the IVCES items, ICC = 0.875 was obtained. The validation of the game by the target population could not be contemplated. Final considerations: The game “Help: Cardiac Arrest!” was considered valid by expert judges, being its use appropriate to promote strategies of teaching and learning in an immersive, interactive and creative way. Product: The product of this master's thesis consists of the development of didactic instructional material, in the form of a serious game in virtual reality entitled "Help: Cardiac Arrest!", to be applied in training processes in Extra-Hospital Cardiopulmonary Arrest with lay people, available at <https://atomicrocket.itch.io/socorroparadacardiaca> in PC version.
Keywords: Jogos sérios; Tecnologia educativa; Educação em saúde; Realidade virtual; Reanimação cardiopulmonar; Enfermagem; Serious games; Educational technology; Health education; Virtual reality; Cardiopulmonary resuscitation; Nursing; ACCNPQ::Ciências da Saúde::Enfermagem